OPTIMIZATION OF THE ROLES AND RESPONSIBILITIES OF INFECTION PREVENTION AND CONTROL NURSE IN HOSPITAL - Marthalena Siahaan; Hanny Handiyani; Nurdiana Nurdiana (Alta Dharma Publisher, 2019)
I Infection Prevention and Control Nurse (IPCN) has an essential role in preventing and controlling infections in hospitals. IPCN's role has been developed to optimize the prevention and monitoring of infection in hospitals. Some countries such as Korea, the United Kingdom, Ireland have developed graduate program nurse control specialists by obtained needs for particular science that can deal with hospital conditions, specifically related to the prevention of infection and care of infectious patients. This case study aims to identify and analyze IPCN's optimization of IPCN in conducting infection prevention and control in a government hospital in Jakarta, which is also a national referral center hospital. Data collection was done by observing the daily activity of the IPCN, reviewing IPCN's role by focus group discussion with nine out of ten IPCNs, and interviewing the nurse committees and director of nursing. The results obtained indicate that the implementation of the functions and roles of IPCN cannot be carried out maximally. This is because, in addition to serving as IPCN, IPCN was also involved in the activities carried out by the unit as well as the implementation of wide surveillance hospitals by the Hospital Infection Control Committee (HICC). It is recommended to optimize the implementation of the functions and roles of the IPCN through the establishment of IPCN competency guidelines aimed at improving IPCN competency standards now and in the future, as well as guiding the determination of IPCN's duties and responsibilities to be more maximal in preventing and controlling infections. Keywords: Hand Hygiene, IPCN, Infection Prevention, and Control, Infection Control